The implicit layout of the dramatic character and its dimensions in the contemporary Iraqi theater text - Mortada Jassim, Ahmed; Mussa Sakran, Riad (Al-Adab Journal, 2020)
This research aims to investigate the implicit format of the dramatic personality, as it constitutes the manifestations of the appointment of the writer in order to bring the selected human entity closer, Where the theatrical text is established within the discourse format of reality from a disguised region that expresses the human psyche, including its tendencies and emotions interspersed with an inter-intellectual debate between the folds of society and cultural components, Its implicit pattern has become one of the most prominent early concepts in monitoring the contradiction of reality, which reflects its image in a way that may not express in all its apparent value towards understanding the reality of human existence. The current research included in it topics of theatrical criticism and its aesthetic and artistic peculiarities. As for its methodological architecture, it was divided into four chapters that included the first chapter, the methodological framework for research that includes, the research problem and the need for it, the importance of research, the aim of the research, and the first chapter concluded by defining the main terms of the research, The second chapter, the theoretical framework, and previous studies included two topics, the first topic came under the title: The implicit format of the theatrical personality, and the second topic titled the dramatic dimensions of the character, followed by what the theoretical framework produced from the indicators and review of the most prominent previous studies. The third chapter (Research Procedures) came to include, the research method, the research tool, the research community, the research sample, the method of selecting a sample, and analyzing the sample. In the fourth chapter, the researcher determined the results, and then the research findings, recommendations and proposals, then a list of research sources followed.